THE IMPACT OF TRUS IN DETECTION OF PROSTATE CANCER IN GEZIRA, SUDAN - D. O, Abuidris; M, El I Mam; E, El Gaylani; A, El Haj (Gezira Journal of Health Sciences, 2010)
Introduction:   Prostate cancer (P ca) is the most commonly diagnosed visceral cancer worldwide. It is the second cause of cancer death in men. Objective: To study the impact of introducing transrectal ultrasound (TRUS)-guided biopsy in detection of Prostate cancer in Central Sudan. Methods : This was a retrospective hospital based study . A review was done for data of prostate cancer patients treated in the Institute of Nuclear Medicine and Oncology & Gezira Hospital of Renal Diseases & Surgery (GHRD&S), Wad Medani, Sudan during the years 2002-2007. Comparison was done between the data available before and after introduction of trans rectal ultrasound biopsy, TRUS in 2005. Results: Prostate cancer cases were contributing for only 8% of all cancers during the time period before TRUS introduction. During the year 2007 the figure increased to 14%. The leading cancer in males now is the P ca. previously it was the third registered cancer before TRUS was introduced. The detection of new cases per year increased dramatically after the introduction of TRUS service. Conclusion and recommendation: Prostate cancer was found to be the most common cancer in Sudanese males. TRUS guided biopsy contributed significantly in early detection of prostate cancer in this region. Distribution of this facility with adequate training of the staff optimizes a proper and early detection of prostate cancer.